Muslimah Indonesian’s Hybridity in John Michaelson's Annisa - Salsabilla, Edla; Handayani, Tuty; Al-Doghmi, Nancy (Muslim English Literature, 2024)
This research aims to analyze how John Michaelson (Muslim British) explores Muslimah Indonesian’s hybridity and mimicry in his novel Annisa (2015). This paper uses close textual analysis by engaging with the postcolonial concepts of Homi K. Bhaba’s hybridity (1994). The analysis focuses on the narrative aspects in Annisa which portrait the hybridity and mimicry of Muslimah Indonesian protagonist, Annisa. The results indicate that; 1) Hybridity is portrayed through the protagonist’s fashion style, education, and language. Mimicry is described through Annisa’s imitating the ideology, romantic relationship, and lifestyle of Western society; 2) Annisa negotiates hybridity and mimicry through her fearlessness to voice injustice against the reductionist views of Indonesia and Islam in orientalist debates. In conclusion, the portrayal of hybridity and mimicry is negotiated when Annisa rejects the power of Western cultural influence to weaken the original culture of Indonesian society by providing lightening assessments of her culture and religion.